Die neue generalistische Pflegeausbildung in Bremen. Gute Ausbildungsqualität - Ergebnisse einer Evaluationsstudie - Peter Bleses; Britta Busse; Cora Zenz (Institut Arbeit und Wirtschaft (IAW), Universität Bremen und Arbeitnehmerkammer Bremen, 2025)
Die seit 2020 umgesetzte "generalistische" Pflegefachkraftausbildung führt drei zuvor getrennte Fachkraftabschlüsse zu einem gemeinsamen Abschluss zusammen. Die neue Pflegeausbildung ist dadurch inhaltlich und organisatorisch sowie in den Lernanforderungen komplexer geworden. Die vorliegende Studie hat aus einer arbeitswissenschaftlichen Perspektive untersucht, welche Auswirkungen die Reform im Land Bremen auf die Ausbildungsqualität als wichtige Variable für den Ausbildungserfolg der Pflegeauszubildenden hat. Was sind die größten Herausforderungen? Welche Rahmenbedingungen sind wichtig, damit möglichst viele Auszubildende die Ausbildung erfolgreich durchlaufen und anschließend auch als Pflegefachkräfte arbeiten wollen? Zentrales Ergebnis der Studie ist die Feststellung großer Ressourcenunterschiede sowohl bei Auszubildenden als auch bei den Lernorten Pflegeschulen und Praxiseinrichtungen, die einen erheblichen Einfluss auf die Ausbildungsqualität besitzen. Zentrale Empfehlung bildet die Etablierung eines lernortübergreifenden Unterstützungskonzepts zur Förderung der Sprachkompetenz und Ausbildungsfähigkeit bereits vor dem Start und begleitend zur Ausbildung. Wichtig wären zudem eine sozialpädagogische Betreuung an den Schulen sowie die Sicherstellung einer qualitativ hochwertigen und verlässlichen Praxisanleitung. – – The Nursing Professions Reform Act of 2017 merges the three previously separate specialist nursing qualifications ('geriatric nursing', 'healthcare and paediatric nursing' and 'healthcare and nursing') into a joint 'generalist' qualification under the title 'nursing specialist'. Completing a nursing specialist training programme qualifies graduates to work in all major care areas. An important aim of the training reform is to achieve progress in training and working conditions in inpatient long-term care and outpatient care, where the quality of working conditions lags behind acute care in hospitals for various reasons. Outpatient and inpatient long-term care facilities must now catch up in order to be able to compete for generalist trained nursing staff. The new nursing training has become more complex in terms of content, organisation and learning requirements as a result of the merger. It involves trainees with different school-leaving qualifications and training locations, who have to cope with the increased requirements with different resources. As the reform of nursing training implemented by federal law is being implemented in each of the federal states with its own specifics and encounters different structures and resources of nursing organisation and nursing training in the various states and municipalities, this study asks from an occupational science perspective: How does the reform in the state of Bremen affect the quality of training as an important variable for the training success of nursing trainees? What are the biggest challenges? In view of the high drop-out rates in nurse training in the state of Bremen, how can it be ensured that as many trainees as possible successfully complete their training and subsequently want to work as nurses? In order to clarify these questions, a threeyear accompanying research project on generalist nursing training was launched in 2021 as part of a research project commissioned by the Bremen Chamber of Labour and completed in summer 2024. The central result of the study is the identification of major differences in resources among trainees and at the learning locations of nursing schools and practice centres. The larger the learning location, the better the staffing in various functions, the higher the trainees' school-leaving qualifications and the better their German language skills, the greater the likelihood of being able to complete the training programme well. There are considerable differences between the care sectors. Acute care has better resources than inpatient long-term care and outpatient care, especially when it comes to smaller facilities. This is also reflected in the quality and scope of practical instruction and teaching staff, the equipment of the learning locations (e.g. skills labs) and the management of the organisational workload. The central recommendation for improving the quality of training and equal opportunities for trainees and learning centres is the establishment of a cross-learning centre support concept for language support and training skills. This support should start as early as possible before the training programme in order to give trainees a good start to their training and accompany them into training as required. A great deal of importance is also attached to the provision of socio-educational support at schools and the expansion of high-quality and reliable practical guidance.
Keywords: 330